Variation in French Interlanguage in Sri Lanka: A Sociolinguistic Study of Omission of ne - Gunawardena, C. (University of Kelaniya, 2015)
The behavior of non-native speakers in relation to sociolinguistic variables has been the focus of many studies (Trevise & Noyau, 1984; Dewaele & Regan, 2002; Regan, 1995, 1996, 1997; Dewaele, 2004; Sax 2001), but the previous studies on interlanguage have focused on corpora derived mainly from immersion students who speak European languages. There have been, to date, virtually no variationist studies on the use of French sociolinguistic variables by Sinhala- speaking advanced learners. The present study examines the sociolinguistic variable: the use of ne in a corpus of advanced French interlanguage produced by 15 learners. A sample of fifteen Sinhala- speaking advanced learners from the University of Kelaniya was used for the study. The researcher recorded the participants’ conversations in an informal setting. Informal speech was collected in one-to-one conversation between the researcher and informants. It is well know that informal speech style can best be obtained in spontaneous speech (Coveney, 1996), therefore the researcher asked questions related to the informants’ immediate environment. Informants were recorded using a simple voice recorder and each recording lasted about thirty minutes. Since it is time-consuming, the researcher transcribed only the occurrences of variables which he intended to analyze. The main research question of this project was: To what extent does variation in the speech of L2 users of French in Sri Lanka reflect the patterns of variation found among L1 users of French? Comparing the native and non-native speakers’ behaviour in relation tothe sociolinguistic variable provided important findings useful for teachers, students and curriculum designers. The researcher found that the omission rate of ne is very low among Sri Lankan learners of French and there was no difference between the omission rate among male and female learners.
Keywords: interlanguage,sociolinguistic variables, learners, corpus, non-native speakers